Multiple oscillators underlie circadian food anticipation in mice - David E. Ehichioya; Ishrat Masud; S.K. Tahajjul Taufique; Melody Shen; Sofia Farah; Shin Yamazaki (Neurobiology of Sleep and Circadian Rhythms)
Circadian pacemakers orchestrate behavioral and physiological rhythms, enabling organisms to anticipate daily reoccurring environmental events such as light and dark, temperature changes, and food availability. When nocturnal rodents are subjected to time-restricted feeding during the day, they typically display food anticipatory activity several hours before mealtime. Upon releasing mice to ad libitum feeding, this anticipatory activity is abolished immediately but, following food deprivation, reappears at approximately the same time. However, the mechanism by which rodents retain this time memory of food availability during ad libitum feeding has remained elusive. We utilized the open-source Feeding Experimentation Device 3 (FED3) to measure food-seeking nose-poking behavior. We programmed the FED3 to dispense a pellet by a single left nose-poke, but not by right poke. During daytime restricted feeding, mice exhibited strong anticipatory nose-poking a few hours prior to the daytime meal in both rewarded left and unrewarded right pokes. In addition, mice also exhibited elevation of both rewarded and unrewarded pokes at night, coinciding with mice's previous habitual feeding time. Following ad libitum feeding, rewarded daytime nose-poking gradually moved back to habitual nighttime. However, following food deprivation, anticipatory poking immediately reappeared during the day and night, coinciding with the times of previous daytime restricted feeding and nighttime habitual feeding. Under ad libitum feeding, db/db mice didn't exhibit a clear daily rhythm in food intake. However, these mice exhibited robust food anticipation in both nose-pokes and activity during daytime restricted feeding. Following release back to ad libitum feeding, db/db mice poked sporadically during the day and night, and following food deprivation, anticipation promptly reappeared. These data suggest that there are at least two oscillators underlying food anticipation: one oscillator with a phase that changes according to food availability, and another oscillator with a phase unaffected by feeding conditions. In db/db mice, the first oscillator is likely impaired, and the second oscillator is unaffected.